RECENT ADVANCES IN MULTILINGUAL WORD EMBEDDINGS: BREAKING LANGUAGE BARRIERS IN AI - Kiran Chitturi (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article explores the transformative impact of multilingual embedding models in natural language processing, focusing on their role in revolutionizing cross-cultural communication and linguistic understanding. It examines recent advances in multilingual model architectures, particularly the BGE M3-Embedding model and BGE-Multilingual-Gemma2, highlighting their capabilities in cross-lingual information retrieval and semantic matching. The article discusses the practical applications of these technologies across various sectors, including education, business, and research, while analyzing their contribution to breaking down language barriers in global communication. Additionally, the article investigates future directions in the field, including multimodal integration, domain adaptation, and improvements in handling low-resource languages, providing insights into the evolving landscape of multilingual natural language processing.